2012
DOI: 10.1590/s1516-35982012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Atualização da proteína ideal para frangos de corte: arginina, isoleucina, valina e triptofano

Abstract: RESUMO -Dois experimentos foram realizados com o objetivo de determinar as relações adequadas de arginina:lisina, isoleucina:lisina, valina:lisina e triptofano:lisina digestíveis para frangos machos nas fases inicial (7 a 21 dias) e de crescimento (28 a 40 dias de idade). Um total de 1.800 frangos no período inicial e de 1.440 no período de crescimento foi distribuído em delineamento inteiramente casualizado com 9 tratamentos e oito repetições de 25 e 20 aves por unidade experimental nos períodos inicial e de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The digestible tryptophan levels found in this study differ from the level found in the studies of Rostagno et al (2011), which suggest 0.200% digestible tryptophan for the starter phase and a tryptophan:lysine ratio of 17%. For feed intake, there was no difference (P> 0.05), which is similar to the results obtained by Campos et al (2012). Among other essential amino acids, tryptophan can be important because of its participation in protein synthesis, and because it is a serotonin precursor, which is related to food intake behavior (HENRY et al, 1992).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The digestible tryptophan levels found in this study differ from the level found in the studies of Rostagno et al (2011), which suggest 0.200% digestible tryptophan for the starter phase and a tryptophan:lysine ratio of 17%. For feed intake, there was no difference (P> 0.05), which is similar to the results obtained by Campos et al (2012). Among other essential amino acids, tryptophan can be important because of its participation in protein synthesis, and because it is a serotonin precursor, which is related to food intake behavior (HENRY et al, 1992).…”
Section: Resultssupporting
confidence: 83%
“…The requirements for chickens can range from 0.16% to 0.19% of digestible tryptophan (BORGES et al, 2002;CAMPOS et al, 2012;DUARTE et al, 2012;ROSTAGNO et al, 2005ROSTAGNO et al, , 2011SIQUEIRA et al, 2011;TAKEARA et al, 2010;VALÉRIO et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Campos et al (2012) determined a 72% SID Ile:Lys ratio for optimal weight gain of 28-to 40-d-old broilers. Similarly, Duarte (2015) recommended an optimum SID Ile:Lys ratio for broiler in the growing-finishing phase at 72%.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous progress of this industry is a result of advances in scientific knowledge and technologies, such as nutrition, which is essential to obtain the best poultry performance (Campos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%